Serum Ferritin as a Predictor of Shock in Children with Dengue Infection - Putri Evalda (Indonesian Journal of Medicine, 2017)
Background: Dengue shock syndrome causes high morbidity and mortality among children worldwide. Several laboratory monitoring can be used to evaluate the progressivity of dengue virus infection. This study aimed to analyze ferritin serum as a predictor of shock in children with dengue infection, and to determine the cut off point that can be used to diagnose dengue shock. Subjects and Method: This was a cross sectional study conducted at pediatric ward, Dr. Moewardi hospital Surakarta Dr. Soetrasno hospital Rembang, Central Java. Study population was children aged less than 18 years old with dengue infection. Study subjects were selected by consecutive sampling. Tha dependent variable was dengue shock. The independent variable was serum ferritin concentration. Mann Whitney test was used to compare mean ferritin concentration between children with and without dengue shock. Cut off point of serum ferritin concentration was determined by ROC curve. Results: Mean serum ferritin concentration in children with dengue shock (mean= 3628.8; SD= 1582.4) was higher than in children without dengue shock (mean= 717.8; SD= 695.8), with p<0.001. Therefore, there was a statistically significant asssociation between serum ferritin concentration and dengue shock . The cut off point of serum ferritin concentration that could be used to show dengue shock with high sensitivity (0.92) and specificity (0.97) was 2304.5. Conclusion: High serum ferritin concentration is a predictor of dengue shock. Keywords: ferritin, dengue shock syndrome, children Correspondence: Putri Evalda. Dr. Moewardi Hospital, Jl. Kolonel Sutarto No.132 Jebres, Surakarta, Central Java 57126. Email: dr. putri.evalda@gmail.com. Mobile: 081227970440